Interhemispheric Endoscopic Fenestration of the Lamina Terminalis through a Single Frontal Burr Hole - Beer-Furlan, André; Pinto, Fernando Gomes; Evins, Alexander I.; Rigante, Luigi; Anichini, Giulio; Stieg, Philip E.; Bernardo, Antonio (Journal of Neurological Surgery Part B: Skull Base, 2014)
Objective We evaluate the feasibility and safety of performing a novel interhemispheric endoscopic fenestration of the lamina terminalis (IEFLT) through a single frontal burr hole immediately lateral to the superior sagittal sinus.Methods Five cadaveric heads underwent IEFLT. Sequential burr holes were made beginning above the glabella and progressed cranially to caudally until the frontal sinus. An endoscope was inserted, and interhemispheric dissection of the arachnoid membranes was completed with endoscopic instruments in a straight direction from the point of entry to the lamina terminalis (LT). Angled optics (0 and 30 degrees) were used to study the neurovascular structures and surgical landmarks.Results The IEFLTs were successfully completed in all specimens and allowed for good visualization of the inferior portion of the LT. The arachnoid dissections were achieved uneventfully. The endoscope provided good surface control of the LT and excellent stereoscopic visualization of the neurovascular complexes. Improved circumferential visualization of the superior part of the anterior portion of the third ventricle was attained.Conclusion IEFLT is a potential alternative to the classic endoscopic third ventriculostomy and a simpler alternative to the subfrontal EFLT, although surgical maneuverability is still limited due to the size of the probe in relation to the narrow surgical corridor.
Keywords: lamina terminalis; endoscopic; fenestration; burr hole; third ventriculostomy